2021
DOI: 10.3390/antiox10020292
|View full text |Cite
|
Sign up to set email alerts
|

Insulin–Mimetic Dihydroxanthyletin-Type Coumarins from Angelica decursiva with Protein Tyrosine Phosphatase 1B and α-Glucosidase Inhibitory Activities and Docking Studies of Their Molecular Mechanisms

Abstract: As a traditional medicine, Angelica decursiva has been used for the treatment of many diseases. The goal of this study was to evaluate the potential of four natural major dihydroxanthyletin-type coumarins—(+)-trans-decursidinol, Pd-C-I, Pd-C-II, and Pd-C-III—to inhibit the enzymes, protein tyrosine phosphatase 1B (PTP1B) and α-glucosidase. In the kinetic study of the PTP1B enzyme’s inhibition, we found that (+)-trans-decursidinol, Pd-C-I, and Pd-C-II led to competitive inhibition, while Pd-C-III displayed mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…In this study, we found its effects on the proliferation and osteogenesis differentiation of hDP-SCs. These studies confirmed that ASP played key roles in combating multiple types of diseases (Ali et al, 2021).…”
Section: Discussionsupporting
confidence: 64%
“…In this study, we found its effects on the proliferation and osteogenesis differentiation of hDP-SCs. These studies confirmed that ASP played key roles in combating multiple types of diseases (Ali et al, 2021).…”
Section: Discussionsupporting
confidence: 64%
“…Docking studies with dihydroxanthyletin-type coumarins—(+)-trans-decursidinol showed that they preferably bound with the active site of Protein Tyrosine Phosphatase 1B. 81 …”
Section: Resultsmentioning
confidence: 99%
“…Docking studies with dihydroxanthyletin-type coumarins-(+)-transdecursidinol showed that they preferably bound with the active site of Protein Tyrosine Phosphatase 1B. 81 Coumarin-cyclic imide conjugates increased the glucose absorption rate to a level that is comparable to metformin in cultured hepatic carcinoma and kidney cells. 82 The furanocoumarin ficusin significantly improved the cellular uptake through the translocation and activation of GLUT4 in the plasma membranes of adipose tissue of diabetic rats.…”
Section: Possible Effects Of Coumarins On Glucose Uptakementioning
confidence: 99%
“…Reducing hepatic glucose generation, increasing insulin production and sensitivity, inhibiting gluconeogenesis, and decreasing glucose absorption are important targets employed in developing synthetic anti-diabetic agents. However, limitations and side effects, such as weight gain, gastrointestinal disorders, headache, peripheral oedema, and hypotension, associated with using these synthetic agents, the cost, and accessibility remain major hindrances [ 45 , 46 ]. Hydrolysis of complex starch, oligosaccharides, and disaccharides by the pancreatic α-amylase, together with glucose uptake by the intestinal α-glucosidase, have been implicated in the postprandial glucose level in type 2 diabetes [ 47 ] with its attendant complications.…”
Section: Discussionmentioning
confidence: 99%